Development of sexual structures influences metabolomic and transcriptomic profiles in Aspergillus flavus. Issue 3 (March 2022) - Luis, Jane Marian; Carbone, Ignazio; Mack, Brian M.; Lebar, Matthew D.; Cary, Jeffrey W.; Gilbert, Matthew K.; Bhatnagar, Deepak; Wientjes, Carol-Carter; Payne, Gary A.; Moore, Geromy G.; Ameen, Yaken Obaydeh; Ojiambo, Peter S.
Abstract: Sclerotium (female) fertility, the ability of a strain to produce ascocarps, influences internal morphological changes during sexual reproduction in Aspergillus flavus . Although sclerotial morphogenesis has been linked to secondary metabolite (SM) biosynthesis, metabolic and transcriptomic changes within A. flavus sclerotia during sexual development are not known. Successful mating between compatible strains may result in relatively high or low numbers of ascocarps being produced. Sclerotia from a high fertility cross (Hi-Fert-Mated), a low fertility cross (Lo-Fert-Mated), unmated strains (Hi-Fert-Unmated and Lo-Fert-Unmated) were harvested immediately after crosses were made and every two weeks until 8 weeks of incubation, then subjected to targeted metabolomics ( n = 106) and transcriptomics analyses ( n = 80). Aflatoxin B1 production varied between Hi-Fert-Mated and Hi-Fert-Unmated sclerotia, while it remained low or was undetected in Lo-Fert-Mated and Lo-Fert-Unmated sclerotia. Profiling of 14 SMs showed elevated production of an aflavazole analog, an aflavinine isomer, and hydroxyaflavinine in Hi-Fert-Mated sclerotia at 4 to 8 weeks. Similarly, genes ayg1, hxtA, MAT1, asd-3, preA and preB, and genes in uncharacterized SM gene clusters 30 and 44 showed increased expression in Hi-Fert-Mated sclerotia at these time points. These results broaden our knowledge of the biochemical and transcriptional processes during sexual development in A. flavus . Highlights: Aflavazole and aflavinine isomer may play a role in formation of sexual structures. MAT1, ayg1, hxtA, preA and preB are genes that could affect sclerotium fertility. Genes in SM gene clusters 30 and 44 may be involved in sexual structure formation.